Pleistocene to holocene expansion of the black-belt cichlid in Central America, Vieja maculicauda (Teleostei: Cichlidae) - McMahan, Caleb D.; Ginger, Luke; Cage, Marcy; David, Kyle T.; Chakrabarty, Prosanta; Johnston, Mark; Matamoros, Wilfredo A. (PLOS ONE, 2017)
The distributions of many Northern Hemisphere organisms have been influenced by fluctuations in sea level and climatic conditions during Pleistocene interglacial periods. These cycles are associated with range contraction and refugia for northern-distributed organisms as a response to glaciers. However, lower sea levels in the tropics and sub-tropics created available habitat for expansion of the ranges of freshwater organisms. The goal of this study was to use ecological niche modeling to test the hypothesis of north to south range expansion of Vieja maculicauda associated with Pleistocene glacial cycles. Understanding the biogeography of this widespread species may help us better understand the geology and interconnectivity of Central American freshwaters. Occurrence data for V. maculicauda was based on georeferencing of all museum records of specimens recovered from FishNet2. General patterns of phylogeographic structure were assessed with mtDNA. Present day niche models were generated and subsequently projected onto paleoclimatic maps of the region during the Last Interglacial, Last Glacial Maximum, and mid-Holocene. Phylogenetic analysis of mtDNA sequence data showed no phylogeographic structure throughout the range of this widespread species. Present day niche models were congruent with the observed distribution of V. maculicauda in Central America. Results showed a lack of suitable freshwater habitat in northern Central America and Mexico during the Last Interglacial, with greatest range expansion during the Last Glacial Maximum and mid-Holocene. Results support the hypothesis of a north to south range expansion of V. maculicauda associated with glacial cycles. The wide distribution of this species compared to other closely related cichlids indicates the latter did not respond to the degree of V. maculicauda in expansion of their distributions. Future work aimed at comparisons with other species and modeling of future climatic scenarios will be a fruitful area of investigation.